Governors-General of the Steppe Region (1882–1917) - V. V. Germizeeva (Омский научный вестник: Серия "Общество. История. Современность")
Based on the prosopographic method, the article describes a collective portrait of people holding a governor-general position in the Steppe Territory in 1882– 1917. Attention is drawn to the educational level, age at the position, personal qualities and activities of officials. The contribution of each of the governors-general to the development of the Steppe Territory is shown. It is disclosed how, under their direct control and guidance, measures were taken for resettlement policy, the development of public education, healthcar and trade